(untitled) (Research, Society and Development, 2022)
This study aims to describe the main public health actions with patients with Diabetes Mellitus through an analysis of the literature. This is a literature review with a qualitative approach carried out in the period of December 2021. It was carried out through articles available in the Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online databases. (MEDLINE) and Scientific Electronic Library Online (SCIELO) that addressed how public health contributes to the control of diabetes mellitus, using the following descriptors: Diabetes mellitus; Public Health using the boolean operator AND. There were a total of 1500 articles that, after applying the inclusion and exclusion criteria, 12 articles were included in the present study after reading them. Throughout the analysis of the articles, it was possible to observe that primary health care is essential for the follow-up of patients with diabetes mellitus and that interventions from primary care are essential for the control of the disease. It was concluded that the follow-up, guidelines, availability of medications contributes to adherence to treatment and control of risks caused by the disease.